If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 1) = 3x + -7x Reorder the terms: 2(1 + 2x) = 3x + -7x (1 * 2 + 2x * 2) = 3x + -7x (2 + 4x) = 3x + -7x Combine like terms: 3x + -7x = -4x 2 + 4x = -4x Solving 2 + 4x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2 + 4x + 4x = -4x + 4x Combine like terms: 4x + 4x = 8x 2 + 8x = -4x + 4x Combine like terms: -4x + 4x = 0 2 + 8x = 0 Add '-2' to each side of the equation. 2 + -2 + 8x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 0 + -2 8x = 0 + -2 Combine like terms: 0 + -2 = -2 8x = -2 Divide each side by '8'. x = -0.25 Simplifying x = -0.25
| 4(2k-5)=4 | | -2(x+3)+4=6(x+3)+8 | | 2x+3x-6=5+4 | | 3(7x+54)=-111 | | 6(3x+2)=72 | | 7x^2-14x-54=2 | | n+50=-12 | | x^2-5x=-7x+3 | | -4x-13=15 | | -6a+3=-9 | | 12=8x-3 | | 5r+7(2r+6)=8r-24 | | 6x-4(7-x)=15 | | -7a+3=17 | | 3x-6=5x+25 | | y^6*y^6=0 | | 3x+13=-23-3x | | 7(x+3)+2=3x+4(5+x) | | 4(x+1)=6x-2 | | 5a+3-2a=a | | 7x+1=3x-20 | | (5a-6)=(564*9) | | 19+8=-3(5x-9) | | -2+4=-8+25x | | -31(-20)+3x+2=38 | | (0.5)2-0.2= | | 3v-9-4v=-(5+v) | | -8x-36=-2(2+8x) | | n+3-7=15 | | -3.19+4.26y-2.71-7.88y= | | 4x-2=16x+4 | | 4x+5=-30-3x |